FAKTOR-FAKTOR RESIKO YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA ANGGOTA POLISI SEKTOR DI SALATIGA - Umi Prihandini; Susi Tursilowati (Poltekkes Kemenkes Semarang, 2016)
Background: Amount 90% of hypertension cases are not clearly known therefore it is also called the silent killer. Pravalensi of hypertension in Salatiga amounted to 32.06%, the figure had exceeded the national rate. This study aims to determine risk factors that may affect the incidence of hypertension among members of the police in Salatiga City, because based of the screening amount 23.5% of police suffered high blood pressure. Methods: Descriptive analytic research in case control study with 1: 2 ratio . The research was conducted on members of police counted 78 respondents. Retrieval of data using measurements of blood pressure, Height, Weight, interviews, and a semi-quantitative food frequency questionnaire to inquire sodium intake. The data obtained and analyzed by univariate, bivariate, and multivariate analyzes. Results: The univariate showed 64% of respondents are current smokers, 60.3% strenuous physical activity, 66.7% malnutrition, and 51.3% sodium intake sufficiently. Chi square analysis showed there was a correlation between smoking and the incidence of hypertension, and correlation between nutritional status and the incidence of hypertension on a police officer. Analysis multivariate showed that nutritional status is the most related factor to hypertension. Conclusion: Factors that causes a person at risk of hypertension are the frequency of smoking and overweight or obesity